Effect of Gibberellic Acid, Nitrogen Fertilizer Treatments, and Interaction Effect on Growth and Productivity of Jew's Mallow (Cochorus Olitorius L.). - Othman, Angel; Samra, Badeeh (Jordan Journal of Agricultural Sciences, 2025)
A field experiment was conducted in Tartous Governorate, in the Al-Drikish area, through out the agricultural season 2024 to compare the effects of gibberellic acid spray, nitrogen soil fertilization, and their interaction on the growth and yield of jew's mallow using a local variety. Hence, A completely randomized design (CRD) was employed. The experiment included nine treatments with three replications: control: G0N0, spray with gibberellic acid). G1N0= 25 ppm, G2N0= 50 ppm (, nitrogen fertilization (G0N1= 15 g/m2, G0N2=25 g/m2( , and interaction treatments (G1N1 ,G1N2 ,G2N1 ,G2N2). The results showed that the treatment with gibberellic acid at 50 ppm showed significant superiority over the other treatments after 60 days of sowing, providing the highest values for all studied vegetative and productive parameters, including: plant height (107 cm), leaf area (977 cm²/plant), length of lateral branches (46.8 cm), plant weight (41.6 g) and yield (2080 g/m2). The interaction effect has shown that spraying with gibberellic acid ( at both 50 and 25 ppm) combined with the highest nitrogen level, 25 g/m², resulted in a significant increase in vegetative growth, and increase in plant weight, and yield compared to the other interaction treatments and control.